LIGHT AS A BUILDING MATERIAL – SUPERIMPOSED VISUALIZATION - Karanakov, Bojan; Aleksandar, Radevski (Ss. Cyril and Methodius University, Skopje, North Macedonia Faculty of Design and Technologies of Furniture and Interior, Skopje, 2022)
This paper aims to investigate and confirm the inseparable connection between: interior architecture, iconographic topography, inverse perspective as a system for representing space on a surface, light and liturgy in Byzantine churches on the territory of medieval Macedonia. The interior architecture in these sacral objects is methodically based on the superposition of all the aforementioned aspects. Any change in one of them can cause a disturbance in a series of others and disrupt the entire system. All these elements are in a methodically created superposition in order to be a visual support for the words of the liturgists and to convey a certain theological thought or concept in the church perceived as a model of the cosmos according to the Orthodox worldview.
Keywords: Light, Byzantine architecture, Inverse perspective, Sacral architecture, Superimposed Visualization